Air quality and ventilation: Exploring solutions for healthy and sustainable urban environments in times of climate change - Iasmin Lourenço Niza; Ana Maria Bueno; Manuel Gameiro da Silva; Evandro Eduardo Broday (Results in Engineering)
Ensuring sustainability and reducing energy consumption in the built environment is essential for achieving energy efficiency and comfort. To obtain a healthy and sustainable urban environment, indoor air quality and ventilation play a crucial role inside buildings since billions of people live in urban environments worldwide and spend significant time indoors. Considering the relevance of this theme, the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) was adopted to conduct a review regarding air quality and ventilation and their impacts on urban environments. The search identified 7568 articles related to the topic, of which 103 were selected after applying the criteria defined to answer four research questions. The main findings of this research are: (I) Analysis of design strategies related to indoor air quality shows that ventilation plays a key role in promoting healthy and comfortable conditions; (II) Air distribution involves controlling temperature, velocity, humidity and pollutant concentration, thus creating an indoor environment with low energy consumption and high air quality; (III) The Covid-19 pandemic has emphasized the urgency of addressing Indoor Air Quality (IAQ) and ventilation as crucial strategies in reducing the spread of respiratory viruses; (IV) Climate change and the global energy crisis have imposed significant pressure on the construction industry to design buildings with low energy consumption, especially in developed countries with high levels of energy consumption.